Pelindungan Bank sebagai Pemegang Hak Tanggungan terhadap Kepemilikan Hak Atas Tanah yang Dibatalkan oleh Badan Pertanahan Nasional Akibat Putusan Pengadilan (Studi Kasus PT X) - Lidya Dwi Putri; Aad Rusyad Nurdin (CV Rewang Rencang, 2024)
Credit is a fundamental function of banks, playing a vital role in fund distribution and economic stimulation, as regulated by the latest Banking Law. Credit is defined as the provision of money or equivalent claims based on a loan agreement, with an obligation to repay with interest. Legal protection for creditors, especially in the execution of collateral, is essential for ensuring fairness and transparency. Execution, though not explicitly defined in Indonesian law, is understood as the implementation of a court decision or the sale of seized property. Property rights, encompassing both collateral rights and enjoyment rights, are central to banking practices for securing debt. Collateral, often in the form of mortgage rights over land, provides a legal guarantee for creditors. While collateral does not transfer ownership, it ensures that creditors' claims are protected in cases of debtor default. Collateral involving property encumbered with mortgage rights is prioritized in protecting banks' interests in credit facilities due to the high economic value of land, which generally appreciates annually. According to Article 4 of Law No. 4 of 1996 on Mortgage Rights Over Land and Land-Related Objects, the types of land rights that can be encumbered with a mortgage include ownership rights, cultivation rights, and building rights. The mortgage holder acts as a preferential creditor with superior rights compared to concurrent creditors (droit de préférence).